2016
DOI: 10.1159/000445775
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Deficits Aggravate Allergic Rhinosinusitis in a Murine Model

Abstract: Objective: Defective innate immune functions can contribute to chronic rhinosinusitis (RS). Recently, it has been reported that chronic RS patients show impaired function of natural killer (NK) cells. We investigated the role of NK cells in eosinophilic inflammation in an allergic RS mouse model. Methods: Mice sensitized to ovalbumin (OVA) by intraperitoneal injection received nasal challenges with OVA for 5 weeks. NK cell depletion was achieved by intraperitoneal injections of anti-asialo ganglio-N-tetraosylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…13 The IL-22-secreting NK22 cells might have a role in the protection of epithelial cell barriers. 14 19,20 Although the percentage of CD56 + NK cells in peripheral blood mononuclear cells (PBMCs) was increased in AR patients, 21 the percentage of CD56 bright subpopulation in total NK cells has been reported to be decreased in AR patients, which might contribute to reduced IFN-c production. 22 ILC1s (non-NK) are analogous to Th1 cells.…”
Section: Nk Cells Represent the Prototypical Member Of Ilc Family Andmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The IL-22-secreting NK22 cells might have a role in the protection of epithelial cell barriers. 14 19,20 Although the percentage of CD56 + NK cells in peripheral blood mononuclear cells (PBMCs) was increased in AR patients, 21 the percentage of CD56 bright subpopulation in total NK cells has been reported to be decreased in AR patients, which might contribute to reduced IFN-c production. 22 ILC1s (non-NK) are analogous to Th1 cells.…”
Section: Nk Cells Represent the Prototypical Member Of Ilc Family Andmentioning
confidence: 99%
“…Kim et al showed that peripheral NK cells from patients with CRS had an impaired effector function reflected by decreased ability to degranulate and to produce IFN‐γ and TNF‐α. This defect was possibly induced by prostaglandin D2 (PGD2), contributed to reduced eosinophil apoptosis, and associated with disease severity in patients with CRS . Although the percentage of CD56 + NK cells in peripheral blood mononuclear cells (PBMCs) was increased in AR patients, the percentage of CD56 bright subpopulation in total NK cells has been reported to be decreased in AR patients, which might contribute to reduced IFN‐γ production .…”
Section: Introductionmentioning
confidence: 99%
“…Natural killer (NK) cells are innate lymphocytes with natural cytotoxicity against infected and cancer cells located in non-lymphoid as well as lymphoid organs. 1 2 3 4 5 NK cells can be subdivided into phenotypically and functionally different populations on the basis of their relative expression of CD56 and CD16 surface markers. More differentiated CD56 dim CD16 + NK cells comprise up to 90% of the peripheral blood NK cells and contain high levels of perforin, granzymes and cytolytic granules.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells control chronic inflammation in airways and act rapidly to eliminate pathogens in acute respiratory infection. 1 2 3 4 5 Asthma and chronic obstructive pulmonary disease (COPD) in the lower airway as well as allergic rhinitis (AR) and chronic rhinosinusitis (CRS) in the upper airway exhibit both similar and different histological and immunological characteristics. 10 11 This review focuses on the role of NK cells in chronic inflammatory airway diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation